MANIFESTASI KULIT AKIBAT ROKOK ELEKTRIK (Media Dermato Venereologica Indonesiana, 2023)
E-cigarettes also known as electronic nicotine delivery systems (ENDS) are device for delivering nicotine and other liquids by using heat energy from battery power using heat energy from battery power by converting liquids into aerosol. E-cigarettes were create as a safer option than conventional tobacco products, meanwhile e-cigarettes still contain toxic and carcinogenic ingredients than conventional cigarettes. E-cigarettes were created as a safer option than alternative tobacco products, although aerosols from e-cigarettes still contain more toxic and carcinogenic ingredients than conventional cigarettes. Harmful effects of using electricity have been reported on the respiratory, cardiovascular and skin systems. Skin disorders caused by e-cigarettes include contact dermatitis, burns, acne, boils, bumps, blisters and disorders of the oral mucosa